Statistical Convergence for Double Sequences in Topological Groups - Sarikaya, Suleyman; Altin, Yavuz (Natl Acad Sciences India, 2026)
In this paper, we define the notions of statistical convergence and lacunary statistical convergence for double sequences using an unbounded modulus function in topological groups. We also show the relations between statistical convergence and lacunary statistical convergence defined in topological groups. In addition, we will examine some inclusion theorems for different unbounded modulus functions.
Keywords: Double sequences; Statistical convergence; Modulus function; Topological groups